A review of reliability analysis of offshore scour protections. Issue 2 (7th June 2019) - Fazeres-Ferradosa, Tiago; Taveira-Pinto, Francisco; Rosa-Santos, Paulo; Chambel, João
Abstract : The R&D project Oracle – offshore risk analysis for climate change adaptation and lifetime extension – is focused on optimising the design of scour protection schemes for the extended lifetime of offshore foundations. This project proposes an optimisation of scour protections by combining reliability-based techniques with the novel concepts of dynamic and wide-graded armour layers. The ultimate goal is to develop a decision support system (DSS) for scour protection design and risk and reliability analysis to be used by professionals and researchers dealing with fixed foundations applied to marine renewable energy projects (e.g. wind, wave and tidal). However, a meaningful implementation of such a DSS implies prior analysis of several knowledge gaps related to scour protection in the offshore environment, which are yet to be fully addressed in the literature. This paper provides a brief review of the scientific and technical challenges in the research field of reliability of offshore scour protection. On the basis of identified challenges, the discussion of future research lines is performed with a particular focus on the aim of the Oracle project. The recent findings related to risk and reliability analysis of offshore scour protection are addressed and framed within the existing knowledge gaps in the literature.